Food reinforcement, dietary disinhibition and weight gain in nonobese adults. (29th May 2013) - Carr, Katelyn A.; Lin, Henry; Fletcher, Kelly D.; Epstein, Leonard H.
<x xml:space="preserve">Abstract</x> Objective Food reinforcement is cross‐sectionally related to BMI and energy intake in adults, and prospectively predicts weight gain in children, but there has not been any research studying food reinforcement as a predictor of adult weight gain. Design and Methods This study examined whether the relative reinforcing value of food versus sedentary activities, as measured on a progressive ratio schedule, predicts 12‐month weight gain in a sample of 115 nonobese (BMI < 30) adults. Dietary disinhibition and dietary restraint were also examined as potential moderators of this relationship. Results In a hierarchical regression controlling for baseline age and weight, dietary hunger, income, sex, and minority status, food reinforcement and predicted weight gain (P = 0.01) significantly increased the variance from 6.3% to 11.7% (P = 0.01). Dietary disinhibition moderated this relationship (P = 0.02) and increased the variance an additional 4.7% (P = 0.02), such that individuals with high food reinforcement had greater weight gain if they were also high in disinhibition. Conclusions These results suggest that food reinforcement is a significant contributor to weight change over time, and food reinforcement may have the biggest effect on those who are most responsive to food cues.